2017
DOI: 10.1002/ets2.12121
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Paths to Diversity: Exploring and Implementing Effective College Admissions Policies

Abstract: pic@ets.orgCopies can be downloaded from:www.ets.org/research/picThe views expressed in this report are those of the author and do not necessarily reflect the views of the officers and trustees of Educational Testing Service. About ETSAt ETS, we advance quality and equity in education for people worldwide by creating assessments based on rigorous research. ETS serves individuals, educational institutions and government agencies by providing customized solutions for teacher certification, English language learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…Consider legal action to reverse the state bans on affirmative action. In the first extensive and up-to-date review of alternative paths for racial diversity, leading scholars explore the most popular alternatives to affirmative action (top percentage programs, socioeconomic status as a proxy for race, and targeted pre-college training and recruitment outreach programs) and found, "that the alternatives are inefficient, cumbersome, and costly and that they do not accomplish the goal" (Orfield, 2017). We encourage the University of Michigan, and other leaders in the "Too Many to Count" 59 higher education community, to consider taking on a leadership role in this civil rights issue by being more active and overturning alternative systems that are ineffective.…”
Section: With Regards To Recruiting More Latinx Students We Recommendmentioning
confidence: 99%
“…Consider legal action to reverse the state bans on affirmative action. In the first extensive and up-to-date review of alternative paths for racial diversity, leading scholars explore the most popular alternatives to affirmative action (top percentage programs, socioeconomic status as a proxy for race, and targeted pre-college training and recruitment outreach programs) and found, "that the alternatives are inefficient, cumbersome, and costly and that they do not accomplish the goal" (Orfield, 2017). We encourage the University of Michigan, and other leaders in the "Too Many to Count" 59 higher education community, to consider taking on a leadership role in this civil rights issue by being more active and overturning alternative systems that are ineffective.…”
Section: With Regards To Recruiting More Latinx Students We Recommendmentioning
confidence: 99%
“…Scholars examining the influence of cases like Bakke and Grutter, for example, show that the ability to consider race as one of many factors in admissions has helped increase enrollments of students of color at selective institutions nationwide (Bowen & Bok, 1998;Garces, 2012b;Welch & Gruhl, 1998). Conversely, studies examining the effects of state laws and policies that prohibit race-conscious admissions reveal a widespread decline of racial and ethnic diversity at selective undergraduate institutions (e.g., Backes, 2012;Hinrichs, 2012;Kidder & Gándara, 2017;Long & Tienda, 2008), in graduate fields of study (Garces, 2012a(Garces, , 2013, and in the professions of law and medicine (Garces & Mickey-Pabello, 2015;Wightman, 1997). Relatedly, a rich body of work has found that high-profile admissions practices that do not explicitly consider race and are ostensibly race-neutral, such as percentage plans and those that consider socioeconomic status, are not effective substitutes for the consideration of race in maintaining campus diversity (Flores & Horn, 2015;Kidder & Gándara, 2017;Reardon, Baker, Kasman, Klasik, & Townsend, 2015).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Conversely, studies examining the effects of state laws and policies that prohibit race-conscious admissions reveal a widespread decline of racial and ethnic diversity at selective undergraduate institutions (e.g., Backes, 2012;Hinrichs, 2012;Kidder & Gándara, 2017;Long & Tienda, 2008), in graduate fields of study (Garces, 2012a(Garces, , 2013, and in the professions of law and medicine (Garces & Mickey-Pabello, 2015;Wightman, 1997). Relatedly, a rich body of work has found that high-profile admissions practices that do not explicitly consider race and are ostensibly race-neutral, such as percentage plans and those that consider socioeconomic status, are not effective substitutes for the consideration of race in maintaining campus diversity (Flores & Horn, 2015;Kidder & Gándara, 2017;Reardon, Baker, Kasman, Klasik, & Townsend, 2015). This body of work shows that the most effective means of generating racial and ethnic campus diversity are those that combine the consideration of race with other factors.…”
Section: Relevant Literaturementioning
confidence: 99%